Communication, Social Networks and Sustainable Development Goals: A Reflection From the Perspective of Social Marketing and Happiness Management in the General Elections in Spain - Galiano-Coronil, Araceli; Jiménez-Marín, Gloria; Elías Zambrano, Rodrigo; Tobar-Pesántez, Luis Bayardo (Frontiers in Psychology, 2021)
The challenges imposed by the global development agenda imply reflecting on the role and contribution of political parties to development processes in the online environment. Social networks have been characterised as a part of the strategies of political campaigns, as it allows political leaders to establish bidirectional communication with citizens. In this context, the present study aims to empirically explore the leading Spanish political formations' publications from a social marketing perspective. In this way, it will be possible to verify how issues related to the Sustainable Development Goals (SDGs) are addressed. On the one hand, this requires elaborating the communication profiles of the main political parties presented to the Spanish General Elections from 2015 to 2019. On the other hand, to analyse whether social themes better discriminate or distinguish one political party from another. For this purpose, a methodology based on text mining, content analysis from a quantitative and qualitative approach, and simple correspondence analysis has been used. Finally, it should be noted that the results of this research show that there are differences between political parties according to the social issues published, with a divergence between the social issues that provoke a better reaction from the public and those most published on Facebook.